Golimumab induction and maintenance for moderate to severe ulcerative colitis: results from GO-COLITIS (Golimumab: a Phase 4, UK, open label, single arm study on its utilization and impact in ulcerative Colitis). Issue 1 (7th July 2018) - Probert, Christopher SJ; Sebastian, Shaji; Gaya, Daniel R; Hamlin, P John; Gillespie, Gillian; Rose, Anita; Tate, Helen; Wheeler, Colin; Irving, Peter M
Abstract : Objective: GO-COLITIS aimed to measure the effectiveness of subcutaneous golimumab in tumour necrosis factor-α antagonist–naive patients with moderate to severe ulcerative colitis (UC) despite conventional treatment. Design: GO-COLITIS was an open label, single arm, phase 4 study with a pragmatic design which reflected UK clinical practice. Adult patients were eligible if diagnosed with UC ≥3 months, partial Mayo score (PMS) 4–9. Patients received subcutaneous golimumab induction (200 mg initially and 100 mg at week 2) followed at week 6 by 50 mg or 100 mg (depending on weight) every 4 weeks until week 54 with a 12-week follow-up. Efficacy was measured by PMS at baseline, week 6, 30, 54 and 66. Health-related quality of life (HRQoL; Inflammatory Bowel Disease Questionnaire (IBDQ) and EuroQol Group 5 Dimensions Health Questionnaire (EQ-5D)) was assessed at baseline, week 6 and week 54. All safety adverse events (AEs) were recorded. Results: 207 patients were enrolled and 205 received golimumab (full analysis set (FAS)205). At week 6, 68.8% (95% CI 62.0% to 75.1%) and 38.5% (95% CI 31.8% to 45.6%) of patients were in response and remission, respectively, using PMS. At the end of the induction phase, 140/141 patients in clinical response continued into the maintenance phase (Maintenance FAS). Sustained clinical response through week 54 was achieved in 51/205 (24.9%) of the FAS205 population and 51/140 (36.4%) of the Maintenance FAS population. Statistically significant improvements from baseline to week 6 were observed for the IBDQ total score and for each IBDQ domain score (bowel symptoms, emotional function, systemic symptoms and social function), as well as the EQ-5D index score and associated visual analogue scale score (p<0.0001). Improvement of HRQoL was sustained through week 54. Serious AEs leading to treatment discontinuation occurred in 8.8% of patients. Conclusion: In this study measuring patient-reported outcomes in patients with moderate to severe UC, golimumab induced and maintained response as measured by PMS and significantly improved quality of life measures. Trial registration number: NCT02092285 ; 2013-004583-56.